The influence of maternal levels of vitamin D and adiponectin on offspring's health - Primož Budič; Darja Paro-Panjan; Kristina Duh; Aneta Soltirovska-Šalamon (Elsevier, 2022)
Background: From the very beginning of life, biological events in the intrauterine environment influence the developing child, its growth, maturation and adaptation. The aim of this study was to assess the impact of maternal vitamin D and adiponectin status on offspring growth, general and bone health. Methods: 162 healthy pregnant women were included in the study, with their vitaminD and adiponectin levels measured in the 32 nd week of pregnancy. Body weight and bone mineral density measurements of their offspring were performed at birth and at the age of three, six, nine and twelve months. Information on children's infectious, allergic and chronic disease was collected from their medical records. Results: Vitamin D insufficiency/deficiency was present in 44% of pregnant women. There was no significant association between maternal vitamin D during pregnancy and offspring body weight at birth or later, as well as between maternal vitamin D and newborn bone mineral density. Additionally, there was no significant association between maternal vitamin D and infectious, allergic or other chronic diseases in offspring. A negative correlation between maternal adiponectin and offspring's body weight at birth was observed (r = - 0.37, p = 0.002), while association with bone mineral density in newborns was not significant. Conclusion: Despite the significant prevalence of vitamin D insufficiency among pregnant women, it did not influence growth or health of their offspring in this study. Maternal adiponectin levels showed an inverse relationship with birth weight of the infants, which may highlight the important link between maternal health and the offspring's growth.